The overview of implementation of the vehicle tax collection in increasing revenue - Tresnawati, Rina (Opción, 2019)
The article aims to investigate the overview of the implementation of the vehicle tax collection in increasing revenue via a descriptive method of analysis. The results showed that the Revenue Service of West Java Province has carried out the collection of vehicle tax in accordance with Law No. 28 the Year 2009 on Regional Taxes and retribution using Official Assessment System. In conclusion, target and realization of the Vehicle Tax reception at the West Java Provincial Revenue Service shows that Vehicle Tax is a local tax which is a great potential for improving revenue.